Effects of perioperative treatment of resectable adenocarcinoma of esophagogastric junction by immunotherapy (Adebrelimab) combined with chemotherapy (XELOX): protocol for a single-center, open-labeled study (AEGIS trial, neoadjuvant immunochemotherapy) - Yingyi Li; Yuqin Cao; Xipeng Wang; Chengqiang Li; Liqin Zhao; Hecheng Li (BMC Cancer)
Abstract Background For resectable adenocarcinoma of the esophagogastric junction (AEG), current treatment exploration primarily focuses on perioperative chemotherapy regimens combined with PD-1/PD-L1 inhibitors, but the long-term survival benefits of still require further investigation, and the use of upfront immunotherapy is typically restricted to patients with metastatic MSI-H (M1 MSI-H) disease due to their potential responsiveness to immunological agents. Adebrelimab, as a novel PD-L1 antibody, has not yet been proven for its efficacy and safety in adenocarcinoma of the esophagogastric junction. Methods The AEGIS study is a prospective, open-labeled, single-arm, phase II clinical trial. A total of 26 patients with AEG will be enrolled. The primary endpoint is the pathologic complete response (pCR) rate after perioperative neoadjuvant immunochemotherapy. Secondary outcomes of the study include the objective response rate (ORR), R0 resection rate, major pathological response (MPR) rate, and pCR rate in combined positive score(CPS) ≥ 5 and MSI-H populations, event-free survival (EFS), and overall survival (OS). The exploratory outcomes are the biomarkers related to therapeutic efficacy, such as PD-L1 expression, microsatellite instability (MSI), tumor mutational burden(TMB), Epstein-Barr virus(EBV) infection, and circulating tumor DNA(ctDNA). Discussion This trail aims to verify the efficacy and safety of the perioperative treatment regimen of anti-PD-L1 (Adebrelimab) combined with chemotherapy (capecitabine plus oxaliplatin, XELOX) for patients with resectable AEG. Considering the differences in chemotherapy regimen tolerance between Asian and Western populations, this study intends to evaluate the suitability of Adebrelimab combined with XELOX chemotherapy for the Asian population. Trial registration ClinicalTrials.gov: NCT06482788. The trial was prospectively registered on 22 May 2024, https://clinicaltrials.gov/study/NCT06482788 .